2021
DOI: 10.1186/s40001-021-00539-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 prevention procedures on other common infections: a systematic review

Abstract: Introduction Since the outbreak of the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) began, necessary measures to prevent virus transmission and reduce mortality have been implemented, including mandatory public use of masks, regular hand-sanitizing and hand-washing, social distancing, avoidance of crowds, remote work, and cancellation of public events. During and after the introduction of COVID-19 lockout, we performed a systematic review of available published literature to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 42 publications
2
54
0
2
Order By: Relevance
“…The spread of other infectious diseases cannot be ignored in the context of COVID-19. Studies have shown that these NPIs for COVID-19 may also reduce the incidence of respiratory infectious diseases such as influenza (7), as well as the number of other infectious diseases reported. Similar reports have been reported in the United States (8) and Germany (9).…”
Section: Introductionmentioning
confidence: 99%
“…The spread of other infectious diseases cannot be ignored in the context of COVID-19. Studies have shown that these NPIs for COVID-19 may also reduce the incidence of respiratory infectious diseases such as influenza (7), as well as the number of other infectious diseases reported. Similar reports have been reported in the United States (8) and Germany (9).…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 is an acute respiratory infection caused by the SARS-CoV-2; it emerged as a novel human pathogen in China at the end of 2019 continues to be a pandemic worldwide [ 1 4 ]. The most common manifestations are pneumonia, high fever, myalgia, dry cough, and chest pain [ 5 9 ]. The death rate due to COVID-19 varies from 1% to more than 7%, and respiratory failure is the main cause [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the spreading of the COVID-19 virus is increasing globally, various guidelines are being issued by the World Health Organization (WHO) for disease control and prevention [140,141]. It is a personal feeling that virus prevention can be done by taking some measures and incorporating them into our daily life.…”
Section: Preventive Procedures From Virusmentioning
confidence: 99%